(untitled) (Global Journal of Science Frontier Research, 2018)
Lentil varieties namely Shishir, Shimal, Shikhar and Khajura Masuro-2 were experimented at three locations of Myagdi, Palpa and Gorkha districts adopting mother-baby trial design with primed and non-primed treatments with an objective of identifying and promoting seed priming technology of lentil in rainfed environment of western hills in Nepal. Combined results of mother trials over sites of three districts revealed that in lentil primed seeds flowered and attained maturity 2-3 and 3-6 days earlier compared to non-primed counterpart. In an average grain yield increament was recorded 13.6% and reached up to 19.4% in Shimal due to priming. Both genotype and location specific effect on observed traits due to priming were recorded. Khajura Masuro-2 (1507 kg ha-1) and Shikhar produced highest grain yield under primed and non-primed (1408 kg/ha) situation, respectively. Combined farmers’ feedback from babies showed better germination and good plant stand of soaked seeds over non-soaked. Earlier maturity in Shimal was feedback from 95.8% of the respondents. Better results of primed seeds for grain yield production in Khajura Masuro-2, Shishir, Shikhar and Shimal were claimed by 75.0%, 83.3%, 91.7% and 95.8% of participating farmers, respectively. Huge percentage (91.7 to 95.8 %) of farmers showed their keen tnterest to continue this technology in future, too.